P-cadherin-dependent adhesions are required for single lumen formation and HGF-mediated cell protrusions during epithelial morphogenesis - Sydnie K. Tran; Jessanne Y. Lichtenberg; Corinne E. Leonard; Jessica R. Williamson; Hazel R. Sterling; Grace K. Panek; Amanda H. Pearson; Santiago Lopez; Christopher A. Lemmon; Daniel E. Conway; Priscilla Y. Hwang (iScience)
Summary: During epithelial morphogenesis, in vivo, epithelial cells form cysts enclosing a single, hollow lumen and extend protrusions as a precursor for tubulogenesis. Cell-cell adhesions (e.g., cadherins) contribute to successful execution of these processes; while there are many different cadherins, one less studied cadherin in epithelial morphogenesis is P-cadherin (CDH3). Here, we investigated the role of CDH3 on successful lumen formation and cell protrusions, using three-dimensional cultures of Madin-Darby canine kidney (MDCK) and CDH3 knockout cell lines. We show that depletion of CDH3 leads to perturbations of hollow lumen formation associated with defects in cell protrusions and tubulogenesis, mediated by Rho/ROCK pathway. CDH3 knockout cells exert lower forces on the surrounding environment compared to wild-type cells, suggesting CDH3 acts as a mechanosensor for stable cell protrusion establishment. Together, our data suggest that CDH3 has an essential function during epithelial morphogenesis by contributing to lumen formation and cell protrusions.